“The kids get haggled over”: how institutional practices contribute to segregation in elementary schools - Ramos Lobato, Isabel; Goldbach, Alina; Hanhörster, Heike (Frontiers in Sociology, 2023)
School segregation is a key topic in urban, educational and inequality research. While previous studies have mainly focused on the effects of both parental school choice and residential segregation patterns on the composition of schools, we draw attention to institutional players steering access to elementary schools as one important dimension of institutional discrimination. Combining expert interviews with school principals and the local schools department with a quantitative survey among parents, we scrutinize the interplay between institutional structures and practices and parental school choice strategies. We identify three dimensions of institutional discrimination as being particularly relevant for school access, and thus for school segregation and inequality: a school’s guidelines and strategic objectives in dealing with segregation, the enrollment process, and a school’s profiling and information policies. These factors prove to be rather subtle, yet crucial facets of institutional discrimination, co-producing and perpetuating spatial inequalities.